Depiction of resistance, liberation, and transformation in post-colonial literature - Kenyangi Justine; Johnson Ocan (Journal of Indigenous Culture, Tourism, and Language, 2025)
Purpose: The study lied of analyzing how authors from formerly colonized regions portray the process of resistance against colonial domination, the pursuit of liberation, and the subsequent transformation of both individual and collective identities. Research methodology: The study used a qualitative literary analysis, grounded in post-colonial theory, focusing on prominent works such as those by Chinua Achebe. The study examines these manifest in the narratives of personal and societal transformation, especially as characters navigate the legacies of colonial oppression. Results: The findings showed that post-colonial authors utilize resistance as a means of both rejecting colonial structures and redefining selfhood, while liberation serves as a crucial turning point for cultural reclamation. Conclusions: The study concluded that post-colonial literature remains an essential medium for exploring the complex dynamics of resistance, liberation, and transformation, offering profound insights into the continuing impacts of colonial histories on contemporary identities. Limitations: The study lies in its focus on Anglophone texts, which may overlook the nuances present in works written in other languages. Contribution: The study contributed to post-colonial discourse by deepening the understanding of how transformation is not only a physical but also a psychological and cultural process.